The Author’s Worldview in The Novel of Ketika Lampu Berwana Merah by Hamsad Rangkuti - Chici Al Wafiq; Mukh Doyin; Yusro Edy Nugroho (Universitas Negeri Semarang, 2024)
This research aims to reveal the author's worldview on poverty in the novel Ketika Lampu Berwana Merah by Hamsad Rangkuti. In addition to these objectives, the results of this research are also expected to be useful for increasing knowledge and increasing appreciation of the author and his works. This research uses a mimetic approach with the theory of literary sociology, the perspective of Goldmann's genetic structuralism theory. The data collection technique in this research is the reading technique (heuristic) and writing from data sources that are considered relevant both from the contents of the novel itself and from other sources. Data analysis in this research uses the genetic structuralism dialectic method to find the meaning and relationship of the novel. The results of this research indicate that the novel Kapan Berwana Merah is the author's worldview on the conditions of poor people, social paradoxes and development at that time. People who are members of capitalist and marginal groups are played by characters who are easily found in urban environments. The number of beggars, poor workers, low education, and widespread hunger show how poverty has become a serious problem in society.